2016
DOI: 10.1016/j.hrthm.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of unilateral temporary stellate ganglion block on human atrial electrophysiological properties and atrial fibrillation inducibility

Abstract: Unilateral temporary SGB prolonged atrial ERP, reduced AF inducibility, and decreased AF duration. An equivalent effect of right and left SGB on both atria was observed. These findings may have a clinical implication in the prevention of drug refractory and postsurgery AF and deserve further clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…4, 19, 20 In humans, unilateral temporary stellate ganglion block might reduce AF inducibility and decrease AF duration. 21 The neural mechanisms of AF is further substantiated by randomized controlled clinical trials that showed pulmonary vein isolation (PVI) plus GP ablation offered a 20–25% higher success rate compared to PVI alone in patients with AF. 22, 23 Another randomized trial showed that botulinum toxin injection in epicardial fat pads can prevent recurrences of AF after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4, 19, 20 In humans, unilateral temporary stellate ganglion block might reduce AF inducibility and decrease AF duration. 21 The neural mechanisms of AF is further substantiated by randomized controlled clinical trials that showed pulmonary vein isolation (PVI) plus GP ablation offered a 20–25% higher success rate compared to PVI alone in patients with AF. 22, 23 Another randomized trial showed that botulinum toxin injection in epicardial fat pads can prevent recurrences of AF after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study was done in 2018 by Lefthiorites et al [10]; it involved the electrophysiologic properties of the left atrium and the inducibility of AF in 36 patients who suffered paroxysmal atrial fibrillation. The study denoted that unilateral SGB reduced the effective refractory period of the left atrium, shortened the duration and the incidence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation as the most common postoperative arrhythmia can be inhibited through SGB. Such block can regulate the autonomic and immune function in such a way to prevent the occurrence and maintenance of AF [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For the ultrasound-guided SGB, each patient will receive 6 mL 1% lidocaine and 6 mL normal saline at one-week intervals to allow a washout period for the injection. The 1% lidocaine is composed of 2% lidocaine and normal saline in a 1:1 ratio (for example, the 1% lidocaine 2 mL is prepared by combining 2% lidocaine 1 mL, and normal saline 1 mL) [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%